Báo cáo thẩm tra Báo cáo của Chính phủ về công tác giải quyết khiếu nại, tố cáo năm 2017 - Ủy ban pháp luật (2017)
Báo cáo thẩm tra Báo cáo của Chính phủ về công tác giải quyết khiếu nại, tố cáo năm 2017 (Số: 908/BC-UBPL14) ngày 27/10/2017.